THE EFFECT OF PERCEIVED ORGANIZATIONAL SUPPORT ON WORK LIFE BALANCE AND EMPLOYEE PERFORMANCE - Khairunnisak (RADJA PUBLIKA, 2023)
The purpose of this research is to analyze the effect of Perceived Organizational Support on Work-life Balance and Employee Performance. This study used random sampling which was distributed to female health workers in Indonesia. This study uses the Partial Least Square analysis technique using SmartPLS 3.3.9. The results of statistical test analysis using alpha = 0. 05. Meanwhile, the results of this study indicate that perceived organizational support has a positive and significant effect on work-life balance and perceived organizational support has a positive and significant effect on employee performance.